World's greatest dad - McKittrick, Sean.; Kelly, Richard, 1975-; Perell, Tim.; Gertler, Howard; Goldthwait, Bob, 1962-; Williams, Robin, 1952 July 21-; Gilmore, Alexie; Sabara, Daryl; Simmons, Henry, 1970-; Brunskill, Gerald; Magnolia Pictures (Firm); Darko Entertainment (Firm); et al. ([Los Angeles, CA] : Magnolia Home Entertainment, 2009)
Lance Clayton once dreamed of a career as a rich and famous writer. He has only managed to be a single dad, and high-school poetry teacher. Kyle is his only son who is a jackass that won't give him the time of day. Lance is dating Claire, the school's adorable art teacher. She doesn't want to get serious or even acknowledge publicly that they are dating. In the wake of a freak accident, Lance suffers the worst tragedy and greatest opportunity of his life. He is suddenly faced with the possiblility of all the fame, fortune and popularity he ever dreamed of. Now, he just has to live with the knowledge of how he got there.
Title from container.
Special features: Deleted scenes; outtakes; behind the scenes; HDNet: a look at World's greatest dad; "I hope I become a ghost" music video by the Deadly Syndrome; commentary.
Director of photography, Horacio Marquinez ; editor, Jason Stewart ; original score, Gerald Brunskill.
Robin Williams, Alexie Gilmore, Daryl Sabara, Henry Simmons.
MPAA rating: R; for language, crude and sexual content, some drug use and disturbing images.
DVD, NTSC, region 1; widescreen (1.85:1) production; Dolby Digital 5.1, Dolby digital 2.0.
Keywords: Single fathers -- United States -- Drama; High school teachers -- United States -- Drama; Women art teachers -- United States -- Drama; Man-woman relationships -- United States -- Drama; Accidents -- United States -- Drama; Secrecy -- United States -- Drama; Comedy films; Feature films; Fiction films; Video recordings for the hearing impaired